Соціологічне осмислення модернізації сучасного українського суспільства - Петрушина, Т.О. (Наука та інновації, 2020)
Вступ. Попри поширене вживання, поняття модернізації не є чітко визначеним. Конкретизація його
змісту залежить від світоглядної позиції дослідника.
Проблематика. Внаслідок запровадження неоліберальних принципів господарювання відбулося не
вдосконалення суспільства й зростання добробуту населення, а перетворення України в сировинний придаток глобального капіталізму і найбіднішу країну Європи.
Мета. Дослідити суспільну думку щодо модернізації українського суспільства і з’ясувати перспективи вітчизняної науки та інноваційного розвитку України. Матеріали й методи. Аналіз статистичної інформації і наукових публікацій з проблем модернізації,
даних соціологічного моніторингу соціальних змін в українському суспільстві і двох експертних опитувань (науковців НАН України і фахівців з питань інноваційного розвитку). Результати. Доведено, що проведена трансформація українського суспільства за своєю суттю є не
модернізацією, а неоліберальним експериментом під модерністським прикриттям, що відкинув Україну
з когорти найбільш промислово і науково розвинених країн на периферію сучасного світу, призвів до зубожіння і тотальної зневіри більшості громадян. Показано, що у межах існуючої неоліберальної моделі
й укорінення олігархічної влади здійснити модернізацію України і перейти до інноваційного розвитку
неможливо. Вітчизняна наука внаслідок фінансового геноциду й відсутності державної підтримки позбавлена можливості ефективно виконувати свої суспільні функції, зокрема бути одним із вирішальних агентів модернізації суспільства в інтересах усіх громадян.
Висновки. За теорією модернізації як ідеолого-теоретичним конструктом сучасності стоять конкретні
політичні й ідеологічні інтереси великого капіталу. Нав’язана Україні теорія і практика неоліберальної модернізації як основного засобу виходу на шлях успішного соціально-економічного розвитку не виправдала покладених на неї надій і призвела до хронічнокризового стану суспільства. Це вимагає пошуку іншої, альтернативної моделі розвитку. Introduction. Despite its widespread usage, the concept of “modernization” is not clearly defined. Concretization of its meaning
depends on the researcher’s worldview position.
Problem Statement. T he introduction of neoliberal economic principles did not lead to the improvement of society and
the growth of human well-being. It transformed Ukraine into a raw-material appendage of global capitalism and the poorest
country in Europe.
Purpose. To analyze public opinion on the modernization of Ukrainian society and identify the prospects for science and
innovative development in Ukraine.
Materials and Methods. Analysis of statistical information and scientific publications on the problems of modernization,
data of the sociological monitoring of social changes in Ukrainian society and two expert surveys (scientists of the National
Academy of Sciences of Ukraine and specialists on innovative development).
Results. T he author has proved that the transformation of Ukrainian society is not, in essence, a modernization. It is a
neoliberal experiment under the guise of modernism, which rejected Ukraine from the cohort of the most industrially and
scientifically developed countries to the periphery of the modern world, led to impoverishment and total despair of the majority
of citizens. The author substantiates that it is impossible to modernize Ukraine and turn to innovative development
within the existing neoliberal model and the oligarchic power rooting. As a result of financial genocide and the lack of state
support, science in Ukraine is deprived of the opportunity to effectively perform its public functions, in particular, to be one
of the decisive agents of modernization of society in the interests of all citizens.
Conclusions. T he specific political and ideological interests of a global capital stand behind the theory of modernization
as an ideological and theoretical construct of modernity. The theory and practice of neoliberal modernization imposed on
Ukraine as the main mean of reaching the path of successful socio-economic development have not lived up to the expectations
and led to a chronic crisis state of the society. It requires finding another alternative model of development.